Seismic performance enhancement of buildings using multi‐limb brace damper systems. (8th December 2020) - Feng, Huan; Zhou, Fangyuan; Ge, Hanbin; Zhu, Hongping; Zhou, Lemu
Summary: A novel brace system with a displacement amplification mechanism for damper energy dissipation is proposed in this paper. Theoretical mechanism of the multi‐limb brace damper system (MLBDS) is established. Finite element models are established to confirm the effectiveness of the proposed system. The seismic performance of the MLBDS is compared with those of traditional brace damper systems. Comparison results show that MLBDS has an excellent energy dissipation performance. In addition, the dynamic responses of a high‐rise building with the MLBDS installed to seismic excitations are evaluated. The results show that the MLBDS can significantly reduce the dynamic responses of the high‐rise building under strong earthquakes.